Supercharge End-to-Side Nerve Transfer: Systematic Review. (March 2021) - Dunn, John C.; Gonzalez, Gilberto A.; Fernandez, Isaac; Orr, Justin D.; Polfer, Elizabeth M.; Nesti, Leon J.
Background: To decrease the time to reinnervation of the intrinsic motor end plates after high ulnar nerve injuries, a supercharged end-to-side (SETS) anterior interosseous to ulnar motor nerve transfer has been proposed. The purpose of this study was to compile and review the indications, outcomes, and complications of SETS anterior interosseous to ulnar motor nerve transfer.Methods: A literature search was performed, identifying 73 papers; 4 of which met inclusion and exclusion criteria, including 78 patients. Papers included were those that contained the results of SETS between the years 2000 and 2018. Data were pooled and analyzed focusing on the primary outcomes: intrinsic muscle recovery and complications.Results: Four studies with 78 patients met inclusion and exclusion criteria. Most patients (33.3%) underwent SETS for an ulnar nerve lesion in continuity, the average age was 46.5 years, and the average follow-up was 10 months. The average duration of symptoms before surgery was 99 weeks, all patients had weakness and numbness, nearly all (96%) had atrophy, and half (53%) had pain. Grip and key pinch strength improved 202% and 179%, respectively, from the preoperative assessment. The vast majority (91.9%) recovered intrinsic function at an average of 3.7 months. Other than 8% of patients who did not recover intrinsic strength, no other complications were reported in any of the 78 patients.Conclusions: The SETS is a successful procedure with low morbidity, which may restore intrinsic function in patients with proximal nerve injuries.